The Difference in Incidence of Scabies between Conventional and Modern Boarding School - Avidah, Amanatum; Ratnaningrum, Kanti (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
The prevalence of scabies in children is still high in Indonesia, especially in children who live in dormitories such as Islamic boarding schools. Rise of modern boarding school that is claimed to be better than conventional boarding school makes researchers moved to find out whether there are differences in the occurrence of scabies in conventional boarding school and modern boarding school. This study is a descriptive observational study. The sample used was 95 respondents in each boarding schools that obtained by a simple random sampling technique. Research data were collected in the form of questionnaires and examination of the diagnosis of scabies using a dermoscope. The data was analyzed using data tabulation. From 190 respondents, most of the samples were in the age range of 14-16 years (46.8%). Scabies occurred in conventional boarding school were 35.3% (46 respondents), and 9.8% (5 respondents) occurred in modern boarding school. It can be concluded that the occurrence of scabies in modern boarding school is less than in conventional boarding school.